Monitoramento e conservação de cavalos-marinhos (Syngnathidae - Hippocampus reidi (GINSBURG, 1933)) no estuário do rio Vaza-Barris - SE - Franco, Ana Cristina Novelino Penna (2016)
The study was conducted in the Estuarine Complex of Vaza-Barris River, an area near to city of Aracaju, Sergipe State, Brazil. The aim of this study is to analyze the pattern of occurrence, population structure and ecological aspects of H. reidi in order to find out ways for the conservation of these animals. In total 21 monthly samplings from September 2013 to May 2015 were carried out. 473 observations of seahorses were done in three sampling points: Riacho da Baleia point (total of 279 observations), Viral point (total of 105 observations) and Caruara point (total of 89 observations). The length of the seahorses observed ranged from 2.1 cm to 19.2 cm, and the overall length mean was 14.4 cm. All over the sample period more male individuals than female individuals were found likewise more adult individuals than juveniles. The population density showed significant differences according to the collection point, but this has not varied significantly over time. Individuals have been found in stage of the reproductive cycle in almost every month of sampling, and the reproductive peaks occurred in February 2014, July 2014 and October 2014. Starting January 2014, the markings were initiated for the observed organisms using elastomers and 232 individuals were marked. Through the mark-recapture, population density was estimated at 294 fish in Riacho da Baleia point, 69 fish in Viral point and 65 fish in Caruara point. The growth of the tracked organisms showed an average of 0.8 cm per month, and male and female individuals showed quite similar pattern of growth. The variations related to the growth pattern according to size classes was obtained and it showed the highest average growth rates in April, May and June. In total 26 couples, 11 pairs of males, 3 pairs of females, two pairs of males with juveniles and nine groups with three or more seahorses were observed. Throughout time, five couples, two pairs of male with juvenile, in the same way that a pair of males, remained together. The data about the clustering of seahorses indicate that there is fidelity to the partner, and demonstrate the highly structured social behavior of seahorses. The spatial fish distribution in the environment was monitored and the results corroborate the literature as it relates to loyalty to the habitat. No fish recaptured moved to another point monitored within the estuary. It was concluded that there is a population in the estuary of the Vaza-Barris River of seahorses H. reidi which is found throughout the year distributed in patches of low mobility, moving according to the tide and changing location, but always remaining within the same areas. The study area gets the impact of various anthropogenic sources, such as professional and recreational fishing, floating bars, boats navigation and jet-skis, construction of houses and condominiums, requiring actions and policies that limit the multiple uses of the region in order to conserve the biota in general and specifically the species H. reidi, which appears today as vulnerable to extinction. The areas used as home for the populations of seahorses must be delineated and human activities with the greatest impact should be avoided in those locations. Also the removal of mangrove vegetation should be avoided since this substrate is essential for the Seahorses continue surviving on such sites. Through the implementation of community management projects of fishery resources, the H. reidi can become a flagship species for the estuary of the Vaza-Barris River, allowing the implementation of conservation projects and ecotourism in the region.